Spices mixing machine / Ainirul Wahidah 'Aini...[et al.] - 'Aini, Ainirul Wahidah; Yahya, Amira Syahira; Ishak, Nur Amanina; Ahmad Tahlim, Nur Shafiqah (2018)
Spices Mixing Machine is a machine designed in order to facilitate in efficiency of process in food related business. This product was named based on its main function which is to mix all the spices and ingredients needed in preparing cooking paste in a big sized cauldron, directly on heat. This machine comes with special features which are spices compartment, weight setter, cauldron, stirrer and induction stove. Each feature serves different role to make the whole process a lot easier with promising end product. Target market for this product is the entrepreneur of small and medium sized business as this machine is not too complex and barely need an expertise to run it. Besides, the size of this product is not too big and suitable for the production of paste at smaller scale than the one produced by other big companies. One of the advantages own by this product compared to other competitors is in term of its simplicity and accuracy. This machine has a simple mechanism and can be handled by anyone. Other than that, the weight setter allows an accurate amount of spices and ingredients to be added into the cauldron. This is important to ensure thjr same taste of cooking paste produced in every batch. The selling price of Spices Mixing Machine is RM50,000 with the cost of production which is RM15,000 per machine. Hence, the rough profit that will be obtained is RM35,000 for each machine. Other than that, the management team that will handle every procedures from designing the product until the delivery of product to the customers consists of individuals who are expert in each other's field to ensure the production of this machine will run smoothly as planned.